The Effect of Work Motivation and Work Environment on Employee Performance: Study at a two-star hotel in Bandung City - Fitria, Tita; Hardiyana, Aan; Danasasmita, Windi Matsuko; Jatmika, Lungguh (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
The purpose of this study is to determine the influence of work motivation and work environment on employee performance in a two-star hotel in Bandung City by obtaining accurate data and collecting the necessary data for analysis. The objectives of this study are to determine the magnitude of the influence of work motivation, the magnitude of the influence of the work environment on employee performance, and the magnitude of the influence of work motivation and the work environment on employee performance. The method used is quantitative method and data collection method by distributing questionnaires to a population of 40 respondents. This study used correlation analysis, path analysis, and coefficient of determination analysis. Based on the results of the study, it was found that work motivation and work environment obtained fairly good results, while performance did not obtain good results. The correlation between work motivation and work environment showed a positive relationship with a magnitude of 0.896. The coefficient of determination was 78.7%. The direct and indirect influence of work motivation on employee performance was 0.426, and the influence of the work environment on employee performance was 0.361. Therefore, the total influence is 0.787 or 78.7%, while the remaining 21.3% represents other variables that were not examined in this study but also affect employee performance.